A full-scale Russian invasion of Ukraine in 2022: Resilience and coping within and beyond Ukraine - Kimhi, Shaul; Kaim, Arielle; Bankauskaite, Dalia; Baran, Maria; Baran, Tomasz; Eshel, Yohannan; Dumbadze, Salome; Gabashvili, Manana; Kaniasty, Krzysztof; Koubova, Alice; Marciano, Hadas; Matkeviciene, Renata; et al. (Applied psychology. Health and well-being, 2024)
The study examined the resilience and coping of samples from Ukraine and five nearby countries during the war in Ukraine. The research focused on (1) the levels of community and societal resilience of the Ukrainian respondents compared with the populations of five nearby European countries and (2) commonalities and diversities concerning coping indicators (hope, well-being, perceived threats, distress symptoms, and sense of danger) across the examined countries. A cross-sectional study was conducted, based on data collection through Internet panel samples, representing the six countries' adult populations. Ukrainian respondents reported the highest levels of community and societal resilience, hope, and distress symptoms and the lowest level of well-being, compared to the population of the five nearby European countries. Hope was the best predictor of community and societal resilience in all countries. Positive coping variables, most notably hope, but also perceived well-being are instrumental in building resilience. While building resilience on a societal level is a complex, multifaceted task, various dimensions must be considered when planning actions to support these states. It is essential to monitor the levels of resilience, during and following the resolution of the crisis, both in Ukraine and in the neighboring countries.
Keywords: senioři; Russian–Ukrainian war; Russia; Cross-Sectional Studies; hope; psychická odolnost; adaptace psychologická; Ukrajina; mladiství; perceived threats; Hope; Rusko; Middle Aged; mužské pohlaví; průřezové studie; Adult; mladý dospělý; Ukraine; distress; Young Adult; ženské pohlaví; morale; Humans; Adaptation, Psychological; sense of danger; lidé středního věku; well‐being; Resilience, Psychological; dospělí; resilience; Female; Aged; Adolescent; lidé; Male; naděje